Theories, techniques and the formation of German business cycle forecasts: Evidence from a survey among professional forecasters - Jörg Döpke; Ulrich Fritsche; Gabi Waldhof (Hamburg University, Department Socioeconomics, 2017)
The paper reports results of a survey among active forecasters of the German business cycle. Relying on 82 respondents from 37 different institutions, we investigate what models and theories forecasters subscribe to and find that they are pronounced conservative in the sense, that they overwhelmingly rely on methods and theories that have been well-established for a long time, while more recent approaches are relatively unimportant for the practice of business cycle forecasting. DSGE models are mostly used in public institutions. In line with findings in the literature there are tendencies of "leaning towards consensus" (especially for public institutions) and "sticky adjustment of forecasts" with regard to new information. We find little evidence that the behaviour of forecasters has changed fundamentally since the Great Recession but there are signs that forecast errors are evaluated more carefully. Also, a stable relationship between preferred theories and methods and forecast accuracy cannot be established.
Keywords: E32; E37; C83; 330; Forecast error evaluation; questionnaire; survey; business cycle forecast; professional forecaster